2005
DOI: 10.1021/ol050971p
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity-Gated Photochromism of 1,2-Dithienylethenes for Potential Use in Dosimetry Applications

Abstract: [reaction: see text] A novel molecular switching system based on reactivity-gated photochromism operates because a butadiene undergoes a [4 + 2] cycloaddition reaction with a dienophile to produce the photoresponsive 1,2-dithienylethene backbone. The reversible change in color when samples are irradiated with appropriate wavelengths of light occurs only after the Diels-Alder cycloaddition reaction takes place.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
36
0
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(41 citation statements)
references
References 9 publications
3
36
0
2
Order By: Relevance
“…2. Close inspection of the molecular architecture suggested that the C-4 and C-11 stereogenic centers of desired absolute configurations in 1c could be built up from a bis-epoxide (5) and the C-17 stereogenic center might be taken from (R)-propylene oxide (8). Accordingly, the framework of 1c could be disconnected at the carbonecarbon double bond, leading to fragments 2 and 3b.…”
Section: Resultsmentioning
confidence: 99%
“…2. Close inspection of the molecular architecture suggested that the C-4 and C-11 stereogenic centers of desired absolute configurations in 1c could be built up from a bis-epoxide (5) and the C-17 stereogenic center might be taken from (R)-propylene oxide (8). Accordingly, the framework of 1c could be disconnected at the carbonecarbon double bond, leading to fragments 2 and 3b.…”
Section: Resultsmentioning
confidence: 99%
“…A reactivity-gated photochromism of diarylethenes was illustrated recently (Scheme 9) [26]. The bridging unit was modified to butadiene and butadiene's derivatives.…”
Section: Bridging Unitsmentioning
confidence: 99%
“…Up to now, a great deal of photochromic compounds based on spiropyrans, spiroxazine, dithienylethenes, fulgides, and Schiff bases have been extensively investigated [9][10][11][12][13][14][15][16][17][18]. Most recently, the design, synthesis, and study of novel photochromic system attracted particular interest.…”
Section: Introductionmentioning
confidence: 99%